A new species of freshwater shrimp of the genus Micratya (Decapoda: Atyidae: Caridea) from Puerto Rico - Karge, Andreas; Page, Timothy J.; Klotz, Werner (Zootaxa, 2013)
The atyid genus Micratya Bouvier, 1913 was previously considered to be monotypic. The area in which the genus is dis-tributed is limited to the islands of the Antilles and Central America, with the type locality of Micratya poeyi being in Cuba. A recent molecular phylogenetic analysis of atyid shrimps from the Caribbean indicated the probable existence of a second species of Micratya from samples collected in Puerto Rico. Here it is described as the new species Micratya cooki sp. nov., differing from its congener in the armature of the dactyli on the fifth pereiopod, the uropodal diaeresis, the distal margin of the telson and by the spinulation of the appendix masculina in male specimens. Because the type specimens of M. poeyi are most probably lost, a neotype for M. poeyi was designated.